Factors affecting human health in the modern world - Fortunka, Kamila Bożena (Journal of Education, Health and Sport, 2020)
Abstract Introduction: The physical well-being of man and society as a whole depends on many interrelated factors. Recently, increased interest in health and its determinants is a response to the growing pace of people’s lives. Increasingly, society puts health first, which makes us a community of health. Lifestyle accounts for about 60% of health potential. The broadly understood human lifestyle, and, consequently, the state of health conditioned by it, is determined by many factors that can be subject to various modifications and changes. They usually include procedures, stimuli, and responses obtained during socialization. Objective: The goal was to present and characterize factors that directly and indirectly affect human health in the modern world. These factors cause a favorable or unfavorable state of human health. Material and methods: The literature has been analyzed. Books and magazine articles were used. Conclusions: A way of providing healthcare using the ward for its internal state, physical activity, and then create very important health behaviors. An effective method of minimizing health disparities is health education, and the role is to invest in the evolution of health values in the modern world. Do not respect the contract related to a healthy lifestyle, i.e. any negative action, contributes to the risk of civilian disease. Keywords: health, health determinants, health behaviors, lifestyle.